2019
DOI: 10.1590/s1517-707620190002.0665
|View full text |Cite
|
Sign up to set email alerts
|

Properties of concrete manufactured with use of ceramic sanitary ware waste as aggregate

Abstract: In concrete manufacture, cement (Portland type is the most used), water and aggregates (classified into coarse and fine) are used. With the use of several raw materials the generation of waste is inevitable, both in construction and in other sectors, such as the industries producing ceramic materials. Among the types of waste from such industries, can be mentioned the ceramic scrap (from the sanitary ware industry). According to the above, the aim of this research was to study the addition of ceramic scrap as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
(31 reference statements)
0
2
0
2
Order By: Relevance
“…Ademais, de acordo com os autores 2020), a resistência se relaciona com a porosidade da matriz do material, quanto mais poroso menor será a sua resistência mecânica, situação que ocorre nos materiais estudados. A mesma situação ocorre com o resíduo de louça sanitária, que apresenta diminuição da porosidade e aumento da resistência à compressão (ALMEIDA et al, 2019). O resíduo de gesso também apresenta melhora na resistência à compressão, assim como à flexão, porém uma característica da adição deste material é o aumento da fluidez da argamassa, afetando sua trabalhabilidade (CRUZ et al, 2022).…”
Section: Resultsunclassified
“…Ademais, de acordo com os autores 2020), a resistência se relaciona com a porosidade da matriz do material, quanto mais poroso menor será a sua resistência mecânica, situação que ocorre nos materiais estudados. A mesma situação ocorre com o resíduo de louça sanitária, que apresenta diminuição da porosidade e aumento da resistência à compressão (ALMEIDA et al, 2019). O resíduo de gesso também apresenta melhora na resistência à compressão, assim como à flexão, porém uma característica da adição deste material é o aumento da fluidez da argamassa, afetando sua trabalhabilidade (CRUZ et al, 2022).…”
Section: Resultsunclassified
“…According to the microstructure, the improvement in the thickness and modulus of elasticity of the interfacial transition zone (ITZ) between pastes and sanitary ware aggregates explained the increase in concrete strength [79]. Almeida et al [80] found that the 28 d compressive strengths of concrete in which 25%, 50%, 75%, and 100% of the cement had been replaced with sanitary ware coarse aggregates were 3.2%, 7.7%, 5.2%, and 1.4% higher, respectively, than that of the reference concrete. In addition, the use of sanitary ware aggregates did not have a significant impact on the compressive strength of selfconsolidating concrete and high-strength concrete [29,81].…”
Section: Mechanical Properties Of Concrete With Ceramic Waste 41 Comp...mentioning
confidence: 99%
“…A trabalhabilidade do concreto produzido com até 25% de agregado de RLS não foi significativamente afetada, não sendo necessário o aumento de água na mistura (ALMEIDA et al, 2019;MEDINA et al, 2011MEDINA et al, , 2016a.…”
Section: Análise E Síntese Das Conclusõesunclassified